The Effect of Giving Coconut Water (Cocos Nucifera L) to Overcome Dysminorrhea In Students Of SMAN 1 Kragilan Serang Banten - Rizqian, Amalia; Sutarno, Maryati (Universitas Malahayati, 2025)
ABSTRACT Dysmenorrhea has a detrimental impact on adolescent life, including: disrupted activities, lower academic achievement, disrupted performance and sleep quality, negatively impacted mood, and caused anxiety and depression. Management of menstrual pain (dysmenorrhea) can be done with non-pharmacological therapy, one of which is giving coconut water. The purpose of this study was to analyze the effect of giving coconut water (cocos nucifera L) on reducing menstrual pain. The design of this study was a quasi-experimental study conducted at SMAN 1 Kragilan, Banten in July - August 2024. The sample used was 60 female students. The intervention in this study was the provision of 250 ml of green coconut water drunk 2 times a day for 3 days. The outcome in this study was the degree of pain as measured by a verbal rating scale. The analysis used was chi square. In the control group, the majority of respondents had pain intensity above or equal to the average, namely 22 out of 30 female students or 36.7%. Meanwhile, in the intervention group, the lower pain intensity was mostly in the pain category below the average, which was 17 people or equivalent to 28.4%. The results of the study and bivariate analysis obtained odds ratio (OR) 2.7, p value 0.035 <0.05; 95% CI (0.09 - 0.82). giving coconut water intervention will reduce dysmenorrhea pain 2 times compared to not being given coconut water and this result is statistically significant. Keywords: Coconut Water, Cocos Nucifera L, Dysmenorrhea